New approaches to the identification of biomarkers of infection and nerve damage in leprosy - Al-Mubarak, Reem, author; Vissa, Varalakshmi, advisor; Brennan, Patrick, advisor; McNeil, Michael, committee member; Bamburg, James, committee member (Colorado State University. Libraries, 2012)
Leprosy is an ancient disease and the first disease discovered to be caused by a bacterium, Mycobacterium leprae. M. leprae is an obligate intracellular pathogen that targets the Schwann cells in the peripheral nerves. As a result of this infection nerve damage and deformity occur. There are three main obstacles that slow the progress in M. leprae research and diagnosis. The first obstacle is the absence of a good animal model to study host-pathogen interaction. The second is the absence of good biomarkers for leprosy diagnosis and sub grouping. The third obstacle is the inability to cultivate M. leprae in vitro, due to the extreme decay of the M. leprae genome and the resulting decline in the maintenance of metabolic pathways. This research thesis addresses each of these issues in turn. The first goal of this study was to improve using the only available animal model, the nine-banded armadillo (Dasypus novemcintus), by studying its molecular response to infection by M. leprae (host-pathogen interactions). Several molecular techniques were applied based on the new technology of "omics" and the availability of the partial genome sequence of the armadillo. Proteomic and lipidomic mass spectrometric profiles of infected and uninfected armadillo tissue (nerve, liver and spleen) were compared. The first partial armadillo nerve protein library was developed. The protein profile showed increased amounts of immunoglobulins IgG and IgM in the infected nerve. A decrease in a 15 kD protein that could be myelin P2 was observed in the infected nerve. We also detected antibodies against myelin P2 in the sera of leprosy patients. The lipid profile of armadillo tissues showed an increase in certain lipid groups, mainly neutral triacylglycerols (TAGs). These TAGs contained acyl chains of specific lengths and unsaturation (mono-and di-unsaturation) in all three types of infected tissues in comparison to naïve tissues. The lipidomics finding was supported by the detection of increased expression of several genes for unsaturated fatty acids and TAG synthesis such as stearoyl-CoA desaturase 9 (SCD9), elongase 5 (ELOVL5), diacylglycerol acyltransferase (DGAT) and fatty acid desaturase (∆5d) in the infected tissues. The second study focused on identifying needed biomarkers for the diagnosis of leprosy and differentiates between leprosy sub-groupings. In this case a mass spectrometric metabolomics approach was used to study the circulatory biomarkers in the sera of newly diagnosed untreated leprosy patients. We found a significant increase in the abundance of certain polyunsaturated fatty acids (PUFAs) and phospholipids in the high-bacterial index (BI) patients, when compared with the levels in the low-BI leprosy patients. These PUFAs are known to exert anti-inflammatory properties that may promote M. leprae survival. This finding is in agreement with the overall phenotype (increase anti-inflammation and high bacterial load) in the high-BI leprosy patients. The third part of this study addressed the inability to grow M. leprae in culture. Here the hypothesis was that a test of viability (using molecular genetics techniques), in the presence or absence of particular nutrients, would lead to identifying a medium or nutrients required for the in vitro maintenance of M. leprae. Based on the M. leprae genome and the genome-based metabolic databases (Metagrowth), several genes were found to be lost from major metabolic pathways in M. leprae. Therefore, the objective was to provide in the medium those metabolites missing because of the pathway disruption. Different culture media were tested to maintain M. leprae in vitro. The viability of the bacteria in different media formulations was compared based on testing expression of several M. leprae transcripts and the 16S rRNA using quantitative real-time PCR (qRT-PCR). Surprisingly, the results from all of these media trials demonstrated that the simple addition of 2% glycerol to 7H12 media supported M. leprae viability up to 21 days, compared to the basal medium (7H12) that showed a decrease in M. leprae viability after 7 days. On the other hand, the addition of 0.1% sodium thioglycolate to 7H12 media reduced M. leprae viability by 3 and 7 days. Many leprosy patients suffer irreversible peripheral nerve damage resulting in blindness or other disabilities as a consequence of M. leprae infection. Until now the mechanisms of nerve damage have not been fully elucidated due to lack of in vitro condition to cultivate M. leprae and animal model to study host-pathogen interaction. In this research dissertation progress was made to understand M. leprae-pathogen interaction. Using new approaches (metabolomics, proteomics and lipidomics) helped in finding marker (s) for the infection and nerve damage in leprosy.
Keywords: armadillo; biomarkers; host-pathogen interactions; mass spectrometry; metabolomics; Mycobacterium leprae